The Role of Green Accounting and Corporate Social Responsibilities in Tourism Industries in Indonesia: The Travel Cost Method - Tirayoh, Victorina Z.; Herman Karamoy; Christian V. Datu; Christoffel M. O. Mintardjo (Open Access Indonesia Journal of Social Sciences, 2023)
The low quality of local tourist destinations is often seen from the need for more infrastructure, unprofessional management, limited management of human resources, and others. For this reason, attention is needed from not only the government but also the role of the private sector to improve the quality of local tourist destinations. This study aimed to describe the implementation of green accounting through corporate social responsibility (CSR) in improving the quality of the tourism industry in Indonesia with a study in Manado City, North Sulawesi Province. Our study examines the economic value of a tourist destination as one of the requirements for the valuation of CSR as part of green accounting records. Data analysis used the travel cost method (TCM). The total of participants in this study was 112 tourists. Data were collected with collection used a survey. The results of this study provide valuable information to the tourism industry in North Sulawesi, especially in Manado City, regarding the need for CSR funds to develop the tourism industry to improve the quality of the tourism industry and the environment. In conclusion, the business and industrial world in North Sulawesi, including companies that wish to implement corporate social responsibility (CSR) based on the limited liability company law number 40 of 2007, can obtain information for the implementation of this CSR in the tourism industry in North Sulawesi, especially in improving the quality of the tourism industry as well as the environment.